Clinical and neurocognitive issues associated with Bosch‐Boonstra‐Schaaf optic atrophy syndrome: A case study. Issue 1 (15th November 2019) - Bojanek, Erin K.; Mosconi, Matthew W.; Guter, Stephen; Betancur, Catalina; Macmillan, Carol; Cook, Edwin H.
Abstract: Nuclear receptor subfamily 2 group F member 1 (NR2F1) is an orphan receptor and transcriptional regulator that is involved in neurogenesis, visual processing and development, and cortical patterning. Alterations in NR2F1 cause Bosch‐Boonstra‐Schaaf optic atrophy syndrome (BBSOAS), a recently described autosomal dominant disorder characterized by intellectual and developmental disabilities and optic atrophy. This study describes the clinical and neurocognitive features of an individual with a de novo nonsense variant in NR2F1 (NM_005654.5:c.82C > T, p.Gln28*), identified by whole exome sequencing. The patient was diagnosed with autism spectrum disorder (ASD) and unlike most previously reported cases, he had no developmental delay, superior verbal abilities (verbal IQ = 141), and high educational attainment despite reduced nonverbal abilities (nonverbal IQ = 63). He had optic nerve hypoplasia with minimal visual impairment as well as mild dysmorphic features. Compared to both age‐matched individuals with ASD and healthy controls, the patient showed reductions in manual motor speed, accuracy of saccadic eye movements, and rates of successful behavioral response inhibition. Although the majority of previously reported cases of BBSOAS have been associated with more global intellectual dysfunction, we report on a patient with selective disruption of nonverbal abilities and superior verbal abilities.